The Effect of Coal Prices, Company Profitability and Dividend Policy on the Company Value of PT Bukit Asam Tbk - Amalia Utami, Meri (Jurnal Multidisiplin Indonesia, 2024)
The purpose of this study is to obtain empirical evidence of Coal Prices, Profitability and Dividend Policy on PT. Bukit Asam Tbk value listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, the research samples obtained totaled 1 company with quarterly research period from 2012-2022 so that there were 44 units of analysis. The research design was quantitative descriptive. The analysis technique in this research is multiple regression analysis method. The results showed that Coal Price has a significant positive effect, Profitability and Dividend Policy have no effect on PT. Bukit Asam Tbk value. The implication of this research is that companies must pay attention to Coal Price that can affect stock price so that company value can increase.